PENGATURAN PERGESERAN SUDUT FASA 120º SEBAGAI PEMBANGKIT GELOMBANG KOTAK PADA INVERTER TIGA FASA - Septiana, Adella Wulan; Setiono, Iman (Gema Teknologi, 2016)
Adella Wulan Septiana, Iman Setiono in this paper explain that Three phase electricity is widely used in large and home industries. However, not all industries or electricity users can enjoy three-phase resources because the installation is quite expensive. So that the use of a single phase to three phase electric converter is needed. One alternative that can be done is by making an inverter. The inverter is a hardware device that functions to convert direct current (DC) voltage into alternating current (AC) voltage. From the 220 VAC voltage enter the step up transformer then to the rectifier circuit so that the voltage generated is 380V. Then IC 555 is used as a box wave generator with a frequency output of 322.7 Hz. Then the output goes into the IC 74175 flip-flop circuit as a phase shift that produces three outputs, where each output has a high and low value with a frequency of 53.8 Hz. Output from rectifier and 74175 is used as input for IGBT drivers. Keywords: three phase electricity, shift register, flip-flop 74175, inverter.ReferencesAfrizal, Mokhamad Asrul & Ainur Rofiq. Perencanaan dan Pembuatan Modul Inverter 3 Phase sebagai Suplai Motor Induksi pada Penngembangan Modul Praktikum Pengemudi Listrik. Proyek Akhir D3 Teknik Elektro Industri. Surabaya: Politeknik Negeri Surabaya Institut Teknologi Sepuluh November.Agus Cahya & Dedid Cahya. Rancang Bangun Inverter 3 Fasa untuk Pengaturan Kecepatan Motor Induksi. Proyek Akhir Teknik Elektronika. Surabaya: Politeknik Negeri Surabaya Institut Teknologi Sepuluh November.Agus                Rusdiyanto           & Bambang Susanto. Perancangan Inverter Sinusoida 1 Fasa dengan Aplikasi Pemrograman Rumus Parabola dan Segitiga sebagai Pembangkit Pulsa PWM. http://www.telimek.lipi.go.id/xdata/docs/BS18.pdf.Erfan, JC. 2016. Inverter 3 Fasa 220 Volt dengan Output Sinusoidal Frekuensi 50 Hz menggunakan Arduino dengan Teknik Direct Synthesis. Tugas Akhir S1 Teknik Elektro. Surakarta: Universitas Muhammadiyah Surakarta.